Perlindungan Hukum terhadap Para Pihak dalam Kegiatan Sewa Menyewa Kapal di Indonesia - Dina Kristina; John Pieries; Wiwik Sri Widiarty (Syntax Idea)
Indonesia is an archipelagic nation with vast maritime territory. Consequently, maritime transportation plays a crucial role in supporting inter-island connectivity, trade, and various other economic sectors. In this context, ship leasing activities become a key aspect of the maritime industry in Indonesia. This academic article aims to analyze and document the legal protection for the parties involved in ship leasing activities in Indonesia. Ship leasing is a significant sector in the Indonesian maritime industry, involving various businesses and individuals. This research is conducted by delineating the legal aspects related to ship leasing contracts, the rights and obligations of the parties involved, and potential legal protection issues that may arise. The study discusses the legal framework governing ship leasing activities, including provisions regulating the rights and obligations of ship owners, lessees, and other relevant parties. In this research, the role of legal regulations in providing protection to the parties involved in ship leasing activities and the enforcement efforts will be considered. The research will also evaluate the challenges and opportunities faced by the parties in achieving adequate legal protection in ship leasing transactions. The research findings indicate the need for improvements in the implementation and understanding of legal aspects related to ship leasing in Indonesia. This article contributes to a better understanding of the legal framework governing these activities and promotes enhancements in the regulation and practices of the maritime industry.